Editorial - Chou, B. Ralph (Canadian Journal of Optometry, 2017)
The summer of 2017 has been eventful for several reasons. It began with the CAO Congress in Ottawa during the last week of June. The many high-quality educational sessions were punctuated with social events where I talked with many former students. I also enjoyed seeing many members of the UW Optometry class of 1979 [...]